Analysis of the Role of Hedonic Shopping Motivation, Shopping Lifestyle, and Positive Emotion on Impulse Buying: Analisis Peran Motivasi Belanja Hedonis, Gaya Hidup Belanja, dan Emosi Positif terhadap Pembelian Impulsif - Jovita Roseina Nariswari; Nurul Azizah (Academia Open, 2026)
General Background The expansion of popular culture and digitalization has reshaped contemporary consumption patterns, particularly among young consumers who increasingly engage in unplanned purchasing of musician merchandise. Specific Background Within Indonesian music fan communities, official merchandise functions not only as a product but also as a medium of emotional attachment and identity expression, as observed in the Team Hindia Surabaya community. Knowledge Gap Despite growing impulse buying tendencies in music fandoms, limited empirical evidence addresses the internal psychological and lifestyle factors underlying this behavior in Indonesian indie music communities. Aims This study aims to examine the roles of hedonic shopping motivation, shopping lifestyle, and positive emotion in impulse buying of Band Hindia merchandise among Team Hindia Surabaya members. Results Using a quantitative explanatory approach with Partial Least Squares analysis on 285 respondents, the findings show that all three variables are positively and significantly associated with impulse buying, with hedonic shopping motivation demonstrating the strongest contribution. Novelty This research provides context-specific evidence from an Indonesian indie music fan community, extending impulse buying literature beyond general e-commerce settings. Implications The results highlight the importance of emotional experience and shopping-oriented lifestyles in understanding spontaneous merchandise purchasing, offering relevant insights for cultural merchandise marketing and consumer behavior research within fandom-based communities. Highlights: Emotional pleasure during purchasing shows the strongest association with spontaneous buying behavior. Trend-oriented and habitual purchasing patterns are linked to unplanned merchandise acquisition. Pleasant emotional states during shopping coincide with higher tendencies toward spontaneous purchases. Keywords: Hedonic Shopping Motivation, Shopping Lifestyle, Positive Emotion, Impulse Buying